STRATEGI PENINGKATAN ASET PT BPR SYARIAH HARTA INSAN KARIMAH (HIK) CILEDUG - Fajri Ryan Isnandar; Muhammad Firdaus; Agus Maulana (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2016)
The objectives of this study were 1) to analyze the conditions of the performance competition on the financial aspect of BPRS HIK Ciledug and the market leader in BPRS industry; 2) to identify the internal and external factors affecting the corporate development and strategic position of BPRS HIK Ciledug based on these factors; and 3) to formulate an accurate alternative strategy and a priority that can be recommended to the company in achieving its goals. Analysis of the evaluation of internal and external factors based on the components contained in the Shari'ah Maqashid and based on the components on The Porter's Five Forces. The analysis of the company's strategic position based on the market growth rate and relative market share on the internal strength was conducted by using BCG matrix (Boston Consulting Group), and the analysis on the alternative strategy formulation was conducted by using IE matrix (Internal-External Matrix), and the QSPM analysis served to determine the priority strategies to increase the assets of BPRS HIK Ciledug. The main weaknesses that should be handled is the lack of scoring systems of financing and the main opportunity is the great number of written requirements for obtaining the financing provided by its competitors. The prioritized strategies of SRB HIK Ciledug include: 1) product development strategy to create innovative products, 2) Market penetration strategy by changing the amount of share returns, 3) Market development strategy by opening new branches, and 4) Backward, forward and horizontal integration strategies by introducing products to various industries.Keywords:  strategies in increasing assets, sharia community financing bank, BPRS Harta Insan Karimah, QSPM